Kritikan Goldziher Terhadap Riwayat Abu Hurairah: Analisis Terhadap Hadith Anjing Tanaman - Abdul Rahim, Z. N.; Mohd Wazir, N. S.; Solihan, S. B.; Rosman, N. N. N. (Universiti Sains Islam Malaysia, 2024)
In the field of hadith studies, Goldziher has been recognised as one of the modern scholars that excelled and explored in criticizing the hadith. Approaching the hadith with various methods, he was found to produce a novel reading on Islamic literature. By employing the critical historical method, concept of anachronism and principle of analogy, Goldziher paved a new path for the future scholars to examine the hadith in a different approach. One of his popular argument on hadith is his criticism on Abu Hurairah’s narration regarding farm dog. This study aims to explore Goldziher’s criticism on this narration and provide a re-evaluation on Goldziher’s inference concerning the topic. The study is qualitative in nature in which researchers employed a library research method. The study in its finding proposed that Goldziher’s criticism on the narration is based on a fragile argument that could probably be reassessed again.